Mössbauer characterization of the tetraheme cytochrome c3 from Desulfovibrio baculatus (DSM 1743): Spectral deconvolution of the heme components - Ravi, Natarajan (2019)
NIGMS NIH HHS (GM 32187; GM 414821)